2000
DOI: 10.1074/jbc.275.7.4670
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Two Major Sites in the Type I Interleukin-1 Receptor Cytoplasmic Region Responsible for Coupling to Pro-inflammatory Signaling Pathways

Abstract: Type I interleukin-1 receptor is the prototype for a family of proteins, which play a central role in early responses to injury and infection. The similarity of function across the family is reflected in similarity in signaling: all members tested couple to activation of NFB and stress kinases. The coupling to these pathways is mediated by a 200-residue intracellular domain (the Toll/ interleukin-1 receptor domain), in which sequence conservation is primarily confined to three short motifs (boxes 1, 2, and 3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
169
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 277 publications
(180 citation statements)
references
References 45 publications
8
169
0
3
Order By: Relevance
“…The TIR domain, which is functionally important for TLR signal transduction, contains three active motifs: box 1 (FDAFISY), box 2 (LC-RD-PG), and box 3 (a conserved W surrounded by basic residues) [34]. It has been suggested that box 1 and box 2 mediate binding to receptor molecules of signaling transduction pathways, while box 3 has been shown to be primarily involved in directing localization of receptors [34]. These active motifs were basically conserved in CiTLR22 (box 1, Y 802 DAFISY 808 ; box 2, L 832 C-RD-PG 842 and box 3, W 934 surrounded by basic residue K940), and TLR22 of other fish species.…”
Section: Discussionmentioning
confidence: 99%
“…The TIR domain, which is functionally important for TLR signal transduction, contains three active motifs: box 1 (FDAFISY), box 2 (LC-RD-PG), and box 3 (a conserved W surrounded by basic residues) [34]. It has been suggested that box 1 and box 2 mediate binding to receptor molecules of signaling transduction pathways, while box 3 has been shown to be primarily involved in directing localization of receptors [34]. These active motifs were basically conserved in CiTLR22 (box 1, Y 802 DAFISY 808 ; box 2, L 832 C-RD-PG 842 and box 3, W 934 surrounded by basic residue K940), and TLR22 of other fish species.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the prevalent notion that TIR domains are highly conserved, the homology of these regions between TIR-containing receptors is actually relatively low, and although there are more focused areas of conservation in key regions involved in signaling, these TIR domains provide ample room for TLR-type specific interactions with downstream signal components (49). To date, much of our knowledge of these signaling pathways is derived from studies of knockout mice (natural or engineered).…”
Section: Tlr Signaling and Effector Functionsmentioning
confidence: 99%
“…Most TIR Box 2 sequences have a conserved proline, which when mutated to histidine renders the protein unable to signal. The function of Box 3 is not fully understood, although it contains residues important in signaling (based on mutational analysis of the type I IL-1 receptor) (Slack et al, 2000) (Figure 1). …”
Section: Structural Similarity With Interleukin-1 Receptor (Il-1r)mentioning
confidence: 99%